Technoparks as Catalyst for Sustainable Future Innovative Ecosystem in Vocational Schools - Usman, Nasir; AR, Murniati; Irani, Ulfa; Mylostyvyi, Roman; Siswanto, Irman (Jurnal Ilmiah Peuradeun, 2024)
Vocational schools are crucial in creating a skilled and adaptable workforce in an era of rapid technological development and a changing industrial landscape. This study aimed to describe integrating technology park activities to promote sustainability in vocational schools, focusing on the Center of Excellence (CoE) model. This study used mixed methods. The study was conducted at 22 High Vocational Schools (HVS) in Aceh Province, and the subjects of the study were 22 principals, 22 teaching factory coordinators and 110 students. Data collection methods were qualitative and quantitative data analysis using observation, interviews and recording followed by data reduction, data display and conclusions. The study was expected to provide a strategic framework for the sustainable development of vocational schools within the technology park paradigm. Students differentiated skills and characters and HVS collaboration through Techno parks by identifying the curriculum enhancement. The results showed a significant shift in vocational school curricula to more dynamic and technology-based curricula, a positive effect on hard skills (practical skills, technical influence) and soft skills (independence, teamwork, critical thinking) of students and active collaboration done through techno park activities.